Gaya Bahasa dalam Kumpulan Cerpen " Membaca TUHAN Dalam Satu Kata Tanya" Karya E. Nong Yonson - Arni Yunarita Patola; Semuel H. Nitbani; Narantoputrayadi Makan Malay (Jurnal Lazuardi, 2026)
The purpose of this study is to describe the use of language style in the short story collection " “ Reading GOD in a Single Question Word" by E. Nong Yonson. The method used in this research is descriptive qualitative with a content analysis technique. The results show that the author uses twenty-six (26) types of language style. These styles function to deepen the reader’s emotions and emphasize the moral messages contained in each short story.